Strong Antimicrobial Effects of Xanthohumol and Beta-Acids from Hops against Clostridioides difficile Infection In Vivo - Radek Sleha; Vera Radochova; Alexander Mikyska; Milan Houska; Radka Bolehovska; Sylva Janovska; Jaroslav Pejchal; Lubica Muckova; Pavel Cermak; Pavel Bostik (MDPI AG, 2021)
Clostridioides (C.) difficile is an important causative pathogen of nosocomial gastrointestinal infections in humans with an increasing incidence, morbidity, and mortality. The available treatment options against this pathogen are limited. The standard antibiotics are expensive, can promote emerging resistance, and the recurrence rate of the infection is high. Therefore, there is an urgent need for new approaches to meet these challenges. One of the possible treatment alternatives is to use compounds available in commonly used plants. In this study, purified extracts isolated from hops-alpha and beta acids and xanthohumol-were tested in vivo for their inhibitory effect against C. difficile. A rat model of the peroral intestinal infection by C. difficile has been developed. The results show that both xanthohumol and beta acids from hops exert a notable antimicrobial effect in the C. difficile infection. The xanthohumol application showed the most pronounced antimicrobial effect together with an improvement of local inflammatory signs in the large intestine. Thus, the hops compounds represent promising antimicrobial agents for the treatment of intestinal infections caused by C. difficile.